Dipropyl phthalate induces craniofacial chondrogenic defects in zebrafish embryos - Qinyuan Shen; Weitao Hu; Fasheng Liu; Si Dong; Xinya Peng; Yihang Zhong; Chao Chen; Yuhua Zuo; Chenkai Ge; Weirong Li; Wenwen Zha; Zhijun Ye; et al. (Ecotoxicology and Environmental Safety)
Dipropyl phthalate (DPRP), a plasticizer commonly utilized in the plastics industry, has been identified in food and the environment and has the potential to present a hazard to human health and the environment. In this study, the first comprehensive evaluation of DPRP-induced craniofacial chondrogenic defects was conducted using a zebrafish model. Zebrafish embryos were exposed to 1, 2, and 4 mg/L DPRP from 6 to 96 h post-fertilization. At 80 hpf, it was observed that exposure to DPRP resulted in craniofacial developmental malformations, which were mainly characterized by the shortening of the mandibular pharyngeal arches and the inability of the accompanying artery to elongate forward. The resulting phenotype was similar to that of micrognathia syndrome. Transcriptome sequencing and molecular docking analyses revealed that DPRP down-regulated chondrocyte-related genes and induced activation of the FoxO signaling pathway, which in turn interfered with cell proliferation and apoptosis. In this process, DPRP induced elevated levels of oxidative stress in the craniofacial pharyngeal arch while promoting inflammatory responses. This ultimately led to craniofacial chondrogenic malformations in zebrafish. The present study demonstrates that DPRP induces developmental toxicity of zebrafish craniofacial cartilage, which may have adverse effects on other aquatic organisms and humans.